2006
DOI: 10.1158/0008-5472.can-05-1959
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Insulin-like Growth Factors on the Strength of the Relation of Vitamin D and Calcium Intakes to Mammographic Breast Density

Abstract: Diets with higher vitamin D and calcium contents were found associated with lower mammographic breast density and breast cancer risk in premenopausal women. Because laboratory studies suggest that the actions of vitamin D, calcium, insulin-like growth factor (IGF)-I, and IGF-binding protein-3 (IGFBP-3) on human breast cancer cells are interrelated, we examined whether IGF-I and IGFBP-3 levels could affect the strength of the association of vitamin D and calcium intakes with breast density. Among 771 premenopau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 54 publications
3
60
1
Order By: Relevance
“…The lack of evidence reported here between adulthood vitamin D intake and percent breast density is consistent with other studies (Vachon et al, 2000;Thomson et al, 2007). However, other research has suggested that dietary vitamin D and calcium may be related to mean breast density in premenopausal women (Holmes et al, 2001;Berube et al, 2005;Diorio et al, 2006). In one study, the strength of the negative association between dietary vitamin D and breast density was found related to the level of calcium intake in pre-menopausal, but not in postmenopausal women (Berube et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The lack of evidence reported here between adulthood vitamin D intake and percent breast density is consistent with other studies (Vachon et al, 2000;Thomson et al, 2007). However, other research has suggested that dietary vitamin D and calcium may be related to mean breast density in premenopausal women (Holmes et al, 2001;Berube et al, 2005;Diorio et al, 2006). In one study, the strength of the negative association between dietary vitamin D and breast density was found related to the level of calcium intake in pre-menopausal, but not in postmenopausal women (Berube et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…Seven studies have also examined intake of calcium and/or vitamin D, as assessed by Food Frequency Questionnaires (FFQ), in relation to mammographic breast density, which is a strong risk factor for breast cancer (McCormack and dos Santos Silva, 2006). Of these studies, one reported a strong inverse relationship for vitamin D and calcium in both pre-and post-menopausal women (Berube et al, 2004); three showed inverse associations among pre-menopausal but not postmenopausal women (Holmes et al, 2001;Berube et al, 2005;Diorio et al, 2006); a fifth reported no association with 25(OH)D but found that women with the highest levels of both 25(OH)D and calcium intakes had the lowest percent density (Knight et al, 2006); and two reported no associations in either group (Vachon et al, 2000;Thomson et al, 2007). All these studies were cross sectional, that is, they relied on a single assessment of calcium and/or vitamin D intakes close to the time of the mammographic examination.…”
mentioning
confidence: 99%
“…Lai et al (7) found a positive association of the A allele of the single base pair polymorphism at position À202 relative to the CAP site in the IGFBP3 gene (A-202C) with serum levels of IGFBP3 and with PMD in premenopausal women. Whereas they found no association between serum levels of IGFBP3 and PMD, three other studies reported a negative association between levels of IGFBP3 and PMD in premenopausal women (16)(17)(18). This is consistent with the biological theory that IGFBP3 slows breast cell proliferation and promotes apoptosis, inferring that increased levels of IGFBP3 should be protective against breast cancer.…”
Section: Discussionmentioning
confidence: 52%
“…For example, alcohol has been shown to consistently increase breast cancer risk [1] through many proposed mechanisms, including the alteration of estrogen metabolism and receptor status and increased exposure to harmful metabolites that damage DNA [27•]. Other components of the diet, such as vitamin D and calcium, may influence breast density, which is a strong risk factor for breast cancer [28][29][30]. Also, certain nutrients may be more influential on breast cancer risk only after reaching a threshold that promotes tumor development; thus, the baseline rate of consumption in a population may dictate when associations are observed [31].…”
Section: Discussionmentioning
confidence: 99%